2018
DOI: 10.1001/jamadermatol.2018.2756
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Gentian Violet on Apoptosis and Proliferation in Cutaneous T-Cell Lymphoma in an In Vitro Study

Abstract: IMPORTANCE Triggering the extrinsic apoptotic pathway is an effective way to kill cutaneous T-cell lymphoma (CTCL) cells in vitro and ex vivo. OBJECTIVE To compare small molecules that induce extrinsic apoptosis in CTCL to identify and analyze compounds that induce high levels of tumor cell death and block tumor cell growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…13 Our laboratory discovered that it is an NADPH oxidase inhibitor and, as such, found that it has antitumor properties in patients with melanoma and lymphoma in vivo. [14][15][16][17] Based on our work, gentian violet was found to have efficacy against early plaque-stated CTCL. In this case report, we demonstrate remission of advanced CTCL using a regimen containing gentian violet, radiation, and mogamulizumab.…”
Section: Discussionmentioning
confidence: 74%
“…13 Our laboratory discovered that it is an NADPH oxidase inhibitor and, as such, found that it has antitumor properties in patients with melanoma and lymphoma in vivo. [14][15][16][17] Based on our work, gentian violet was found to have efficacy against early plaque-stated CTCL. In this case report, we demonstrate remission of advanced CTCL using a regimen containing gentian violet, radiation, and mogamulizumab.…”
Section: Discussionmentioning
confidence: 74%
“…However, this patient did not show clinical or histopathologic signs of impetiginization (Figs 1 and 2), and GV was not used as an antimicrobial in this case. Rather, the intent was to use the antitumor activities that have been proposed and observed in the literature 3, 6. To our knowledge, this is the first reported case of treatment of MF with GV.…”
Section: Discussionmentioning
confidence: 99%
“…GV also inhibits NF-kB, also possibly through NADPH oxidase inhibition, which has been implicated in proliferation of CTCL tumor cells. A recent report by Wu and Wood 6 found GV to enhance Fas and TRAIL pathway-dependent apoptosis in CTCL cell lines and Sezary syndrome blood samples 6 . Speculation exists regarding a theoretical carcinogenesis risk associated with GV, although this has not be found to exist in clinical practice of the author or in the literature 7 …”
Section: Discussionmentioning
confidence: 99%
“…It is a central mediator of immune and inflammatory responses, and the study by Amitay-Laish et al showed the possibility of MF exacerbation by anti-TNF-α therapy [22]. In an in vitro study of cutaneous T-cell lymphoma, Wu and Wood revealed the induction of extrinsic apoptosis by gentian violet via the Fas and TRAIL (TNF-related apoptosis-inducing ligand) pathways [23].…”
Section: Discussionmentioning
confidence: 99%